Լարային կսմիթային գործիքների պատկերները հնագույն գտածոների վրա և դրանց կապը կիթառի հետ - Մարիաննա Պողոսյան (ՀՀ ԳԱԱ հրատ.)
В данной статье делается попытка приблизиться к разгадке происхождения гитары. В качестве исследуемого материала были выбраны ритуальные сосуды с изображениями древних музыкальных инструментов. This article is concerned with the issue of guitar genealogy. The primary source of Marianna Poghosyan’s research has been ancient artifacts of great historical and cultural value that is ritual goblets with ancient stringed-plucked musical instrument images.
Keywords: Instrumental Techniques; Music